FEATURES OF MORPHOFUNCTIONAL CONDITION OF THE THYROID GLAND AND REGIONAL LYMPH NODE IN NORMAL AND IN HYPOTHYROIDISM - Аbdreshov Serik Nauryzbaevich; Kozhaniyazova Ulbolssin Nurgalievna; Demchenko Georgii Anatolevish; Shynybekov Sholpan Shanovna; Nauryzbai Ulzhan Beibitovna (Academic Journal of Physical and Chemical Sciences, 2020)
The article presents data on the ratio of the functional structures of the lymph nodes in thyroid failure. Taking mercazolilum within 30 days led to a disorder of the morphofunctional condition of the thyroid gland and cervical lymph node. According to histological and morphometric analysis of the thyroid gland, a high sensitivity to monthly exposure of mercazolilum is shown, which is expressed in a synchronous morphological rearrangement of the tissue microdistrict of the thyroid gland and lymph node. Changes were identified especially in the peripheral zones of the thyroid lobes, which led to a decrease in the size of follicles, and in thyrocytes to a change in cellular elements, which caused a decrease in the production of thyroid hormones and developmental disability of reactive and compensatory changes in the thyroid gland. The structurally functional component related to both the thyroid gland and the lymph node is the extracellular space with vascular and non-vascular paths of microcirculation, a change in which leads to disruption of the vesicular-colloid transport in the thyroid cytoplasm and to a change in the functional state of the thyroid gland. There are changes in the regional lymph node, which are characterized by a change in the ratio of cortical and medullary substance, in which the proportion of structures of the cortical substance decreases; there was an increase in the number of macrophages in the lymphoid nodule, the medullar sinus, a decrease in the number of mature plasmocytes, in the paracortex and Billroth’s stand. These changes indicate an immunosuppressive effect on the lymph node. On sections of the lymph node, capsule infiltration with lymphoid elements was often observed. The value of paracortex was statistically significantly reduced. The decrease in the area of the paracortical zone is relative, since it occurs due to the formation of sinuses. Blood vessels are blood-filled in the lymph node. There was an increase in the volume of the lymph node, which leads to a uniform development of the structures of the cortical and medullar substance of the lymph node.